Development and Validation of the Amphetamine-Type Stimulants Motive Questionnaire in a Clinical Population - Thurn, Daniela; Kuntsche, Emmanuel; Weber, Jennifer Anna; Wolstein, Jörg (Frontiers in Psychiatry, 2017)
Approximately 35.7 million people world-wide use amphetamine-type stimulants (ATS) leading to a high demand for effective treatment. Understanding the motives behind ATS use is a necessary basis for preventive and therapeutic treatment. The objective of this study is to develop the Amphetamine-Type stimulants Motive Questionnaire (AMQ) and to confirm its construct and concurrent validity in respect to the first and the latest month of ATS use based on answers of 233 patients with ATS disorders (74.2 % male; mean age: 31.1 years). Confirmatory factor analyses were employed to test for the construct validity of the AMQ. Nested models of confirmatory factor analyses with increasing constraints for gender and age were estimated to test the equivalence of the factor structure in different subgroups. Independent sample t-tests were conducted to test for mean differences in the motive dimensions. A structural equation model was estimated to confirm the concurrent validity using the latent four motive factors (i.e. enhancement, coping, social and conformity motives) as independent variables and frequency of ATS use in the first and the latest month of use as a dependent variable. The results confirmed the AMQ’s four-dimensional factor structure in general, and across gender and age groups for both periods of time. Men (first month: M=4.21, SD=0.75; latest month: M=3.86, SD=0.93) use ATS more frequently due to enhancement motives than women (first month: M=3.85, SD=1.12; latest month: M=3.46, SD=1.29) at both periods of time (first month: t(77)=-2.33, p=0.022; latest month: t(80)=-2.19, p=0.031). Structural equation modeling confirmed an association between coping motives and use frequency, for both periods of time (first and latest month: β=0.32, p<.001), as well as between social motives and frequency of use for the latest month of use (β=0.30, p<.01). To conclude, the AMQ is a valid and reliable instrument for assessing motives of ATS use in a clinical population. It can provide important insights into the motivational structure of the first and latest months of ATS use which are useful for preventive and therapeutic treatments as well as the development of abstinence skills.